Model‐based integration of citizen science data from disparate sources increases the precision of bird population trends. Issue 6 (11th March 2021) - Hertzog, Lionel R.; Frank, Claudia; Klimek, Sebastian; Röder, Norbert; Böhner, Hannah G. S.; Kamp, Johannes
Abstract: Aim: Timely and accurate information on population trends is a prerequisite for effective biodiversity conservation. Structured biodiversity monitoring programmes have been shown to track population trends reliably, but require large financial and time investment. The data assembled in a large and growing number of online databases are less structured and suffer from bias, but the number of observations is much higher compared to structured monitoring programmes. Model‐based integration of data from these disparate sources could capitalize on their respective strengths. Location: Germany. Methods: Abundance data for 26 farmland bird species were gathered from the standardized Common Breeding Bird Survey (CBBS) and three online databases that varied with regard to their degree of survey standardization. Population trends were estimated with a benchmark model that included only CBBS data, and five Bayesian hierarchical models integrating all data sources in different combinations. Across models, we compared consistency and precision of the predicted population trends and the accuracy of the models. Bird species body mass, prevalence in the dataset and abundance were tested as potential predictors of the explored quantities. Results: Consistency in predicted annual abundance indices was generally high especially when comparing the benchmark models to the integrated models without unstructured data. The accuracy of the estimated population changes was higher in the hierarchical models compared to the benchmark model but this was not related to data integration. Precision of the predicted population trends increased as more data sources were integrated. Main conclusions: Model‐based integration of data from different sources can lead to improved precision of bird population trend estimates. This opens up new opportunities for conservation managers to identify declining populations earlier. Integrating data from online databases could substantially increase sample size and thus allowing to derive trends for currently not well‐monitored species, especially at sub‐national scales.